Pengaruh Kepemimpinan, Kompensasi, dan Motivasi Kerja Terhadap Kinerja Karyawan dan Guru Pada Sekolah Dasar Islam Terpadu Deli Serdang - Anfa, Sugianto; Soemitra, Andri; Nurjianti, Widya (Jurnal Ilmiah Ekonomi Islam, 2023)
Effective leaders not only use their power to encourage employee performance but can also provide high motivation, inspiration, and loyalty for employees to be able to devote all of their focus to achieving optimal performance. This study aims to determine the effect of leadership, compensation and motivation on employee performance. The sampling technique in this study is a random sampling technique, namely random sampling from three schools, namely SD IT Alhijrah 2, SD IT Bina Insan and SD IT Deli Insani, totaling 57 samples. The type of research used is quantitative research with multiple linear regression analysis. The data processing process uses SPSS 20. With a constant value of (9,190), it shows a positive value, meaning that if leadership, compensation and motivation are assumed to be constant, employee performance will increase by 9,190 units. The regression coefficient value of compensation is 0.186, this value can be interpreted when leadership increases by 1 unit, then employee performance will increase by 0.186 units. The value of the regression coefficient of compensation is 0.333, this value can be interpreted that when compensation increases by 1 unit, employee performance will increase by 0.333 units. The value of the regression coefficient of motivation is 0.415, this value can be interpreted that when motivation increases by 1 unit, then employee performance will increase by 0.415 units. The results of the study indicate that leadership has a partial effect on performance, compensation has a partial effect on performance, motivation has a significant and partial effect on performance and leadership, compensation and motivation have a simultaneous effect on performance.